Waqf: the implementation of waqf in higher education in UiTM Puncak Alam / Muhammad Ammar Abdullah Zawawi. - Abdullah Zawawi, Muhammad Ammar (2019)
Muslims around the world are exposed to the practice of waqf, but the extent of their knowledge on the practice is difficult to measure. In general, the awareness of the requirement in practicing waqf among Muslims society are important since it is useful to the Muslims and concurrently can help certain those in need. There is a growing number of waqf properties provided from time to time by the Muslims in Malaysia. For educational purposes, some of the waqf assets were reserved because of such scenario, it is important to track the growth of waqf education in Malaysia in order to maintain the good practice and management of waqf property as well as the development of waqf education. The objectives of this research is to identify the waqf according to Islamic perspective and to analyse the implementation of waqf in higher education in UITM Puncak Alam. The problem statement is the people do not know or do not understand the concept of waqf education. It is because it just mainly focuses on education at the lowest level such as school level and covers only religious areas. This is because they lack knowledge and awareness about the waqf. Other than that, the problems faced by society today are that they want a shortcut for success. They just want to know the results and just relax, they do not want to know how the waqf are invested. The research has used data collection methods through interviews and observations with officials working at University of Technology Mara (UiTM) where an interview session was made with a respondent to obtain accurate information. The purpose of this interview is to seek and obtain accurate data from UiTM waqf centers on prohibited elements or conceptual concepts or other types of waqf education. Through this study, waqf education may hopefully be proposed to enhance the growth of the education system and economic development in Malaysia, in particular UITM Puncak Alam.